Oral History, Donor Engagement, and the Cocreation of Knowledge in an Academic Archives - Weaver, Robert G.; Hernández, Zachary R. (Archivaria, 2022)
This article examines attempts at the Southwest Collection at Texas Tech University’s Southwest Collection/Special Collections Library (SWC/ SCL), in Lubbock, Texas, to integrate its oral history program into collection acquisition, arrangement, description, and discovery processes. Beginning with the creation of a staff position dedicated to acquisition, and continuing through an evolution of job duties resulting from COVID-19, the SWC’s oral historians now not only facilitate collection acquisition through extensive relationship building but also engage donors during arrangement and description. Such reconceptions have led to new processes and workflows, wherein oral history has become an endeavour of collaborative knowledge creation and an enabler of a more democratic archives.